Nacionalno i republičko u hrvatskom filmu jugoslavenskog razdoblja - Gilić, Nikica (2008)
Croatian Cinema has fully formed in the socialist Yugoslavia, but very soon the production became more and more diversified, centered around the capital cities of the federal units (Croatia, Serbia, Slovenia...). During the 1960s there was also a tendency to allow for smaller production ventures to take place, so the modernist poetics had a certain amount of liberty in the 60s. However, the unitarist tendencies also took place, particularly in the genre of the partisan film ("partizanski film").